Am I understood? exploring the exercise of discourse competence knowledge in academic writing class presentations - Junaidah Januin; Wan Hurani Osman (Pusat Penataran Ilmu Bahasa, Universiti Malaysia Sabah, 2020)
Completing tertiary class presentations is an inherently complex effort for ESL learners undergoing EAP courses. They are confronted with tasks that require them to search for information, select relevant sources, read and write highly conventional academic genres, and present findings in an academic presentation. Presenting an essay assignment, for example, allows learners to exercise an advanced degree of discourse competence in order to create a well-organized essay. This study presents both observation and interview analyses to uncover the elements of discourse competence knowledge that relate to the exercise of discourse competence knowledge in students’ academic presentations. The study also employs an ethnographic analysis of student’s interviews, pertaining to the process of the essay map presentation. In addition to the interviews, the study also utilises class observations as part of the ethnographic analysis. The observation involved 12 students’ presentations of their essay map. Both document and ethnographic data are analysed using template analysis [see 22,23]. The study's findings suggest that there are three types of discourse competence knowledge underpinning the oral presentation of the essay assignment: public speaking, oral presentation structure, and linguistic knowledge. The implications of the study are threefold: first, students should develop the ability to exercise discourse competence to enable them to present their essay findings more accurately and appropriately; secondly, teachers should have a sound understanding of the discourse competence knowledge in order to help their students to develop and exercise discourse competence; and lastly, syllabus designers need to have a clear conceptualisation of the types of discourse competence knowledge that need to be integrated within the oral presentation section of a syllabus which takes into account all of the types of knowledge engaged in academic presentations.